Accuracy and reliability of radiological methods for assessing fusion rates in patients undergoing spinal arthrodesis and stabilization: a systematic review of the past 10 years - Bilancia, Gabriele; Contartese, Deyanira; Delbello, Federica; Tedesco, Giuseppe; Salamanna, Francesca; Griffoni, Cristiana; Gasbarrini, Alessandro; Giavaresi, Gianluca; Spinnato, Paolo (Frontiers in Surgery, 2025)
BackgroundReliable assessment of spinal fusion remains a significant challenge due to the absence of universally accepted radiological criteria. Despite the widespread use of spinal arthrodesis and stabilization, substantial variability persists in how fusion is defined, assessed, and reported across studies. This systematic review evaluates current radiological methods for assessing spinal fusion outcomes, focusing on their reliability, reproducibility, and clinical applicability, and identifies existing limitations to inform future research and practice.MethodsA systematic search was conducted in PubMed, Scopus, and Web of Science for studies published between 2014 and 2024. Following PRISMA guidelines, clinical studies reporting explicit radiological criteria for assessing spinal fusion at any vertebral level were included. Extracted data comprised study characteristics, imaging modalities, surgical techniques, fusion definitions, and use of validated scoring systems. Risk of bias was assessed using the ROBINS-I tool.ResultsOf 2,965 articles screened, 557 met the inclusion criteria. Only 36.8% of studies used standardized scoring systems—primarily Bridwell, Brantigan-Steffee-Fraser (BSF), and Lenke classifications. In contrast, 61.2% relied on non-standardized or author-defined criteria, contributing to significant methodological heterogeneity. Computed tomography (CT), alone or combined with conventional radiography (CR), was the predominant imaging method (74.5%), while magnetic resonance imaging (MRI) was used in only 2.0% of studies. Over 200 distinct fusion criteria were identified, underscoring the lack of consensus.ConclusionsSignificant heterogeneity persists in the radiological assessment of spinal fusion, largely due to inconsistent use and interpretation of fusion criteria, even among studies employing established scoring systems. This variability limits comparability across studies and underscores the need for consensus-based, validated guidelines. Future research should prioritize the development and standardization of objective radiological criteria to improve the reliability and clinical applicability of fusion assessment in spinal arthrodesis. Emerging technologies, such as Hounsfield unit–based CT metrics and AI-assisted imaging, appear promising for improving diagnostic accuracy.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251111767, PROSPERO CRD420251111767.